2022
DOI: 10.1159/000522393
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Association between Genetic Polymorphisms in the <b><i>CHI3L1</i></b> Gene and Asthma Risk

Abstract: <b><i>Background:</i></b> Chitinase 3-like 1 (<i>CHI3L1</i>) is an important factor involved in the development of asthma. This meta-analysis assessed the association of the <i>CHI3L1</i> polymorphisms rs4950928, rs10399931, rs883125, rs880633, and rs10399805 with asthma risk. <b><i>Methods:</i></b> The literature searches were conducted in PubMed, Web of Science, Wanfang, and China National Knowledge Infrastructure up until September 4, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Cold weather can induce asthma symptoms that are more severe in patients with uncontrolled asthma than in those with well-controlled asthma [13]. Further, more than 100 genes have been shown to cause asthma, such as the BsmI (rs1544410) and ApaI (rs7975232) polymorphisms of the vitamin D receptor gene, the rs20541 and rs1800925 polymorphisms of IL13, and the rs4950928, rs10399931, and rs8883125 polymorphisms of chitinase 3-like 1 [14][15][16].…”
Section: Asthma Inducersmentioning
confidence: 99%
“…Cold weather can induce asthma symptoms that are more severe in patients with uncontrolled asthma than in those with well-controlled asthma [13]. Further, more than 100 genes have been shown to cause asthma, such as the BsmI (rs1544410) and ApaI (rs7975232) polymorphisms of the vitamin D receptor gene, the rs20541 and rs1800925 polymorphisms of IL13, and the rs4950928, rs10399931, and rs8883125 polymorphisms of chitinase 3-like 1 [14][15][16].…”
Section: Asthma Inducersmentioning
confidence: 99%
“…11 Another meta-analysis of 16 publications, comprising 18 studies involving 5005 asthma patients and 9725 controls, demonstrated that the CHI3L1 polymorphisms rs4950928, rs10399931, and rs883125 are vital genetic factors for asthma in East Asian individuals. 12 Using targeted next-generation sequencing (NGS), Liu et al 13 analyzed 211 asthma-related genes selected on the basis of database searches in a cohort of 284 patients with asthma and 205 healthy controls from the Southern Han Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…A meta‐analysis of 11 studies, involving a total of 2895 patients and 2914 controls, identified the IL13 SNP rs1800925 as a risk factor for allergic asthma in the Asian population 11 . Another meta‐analysis of 16 publications, comprising 18 studies involving 5005 asthma patients and 9725 controls, demonstrated that the CHI3L1 polymorphisms rs4950928, rs10399931, and rs883125 are vital genetic factors for asthma in East Asian individuals 12 . Using targeted next‐generation sequencing (NGS), Liu et al 13 .…”
Section: Introductionmentioning
confidence: 99%